The Effect of Satin Fabric Thickness on Bustier Construction Quality Using the Helen Joseph Armstrong Method - Arma Alifia; Yusmerita Yusmerita (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
The bustier is a women’s upper garment designed with a tight fit to conform to the body’s contours, particularly around the bust, waist, and hips. Historically, the bustier was originally used as an undergarment; however, along with the evolution of fashion trends, its design has been modified so that it can also be worn as outerwear, serving to shape the body silhouette for a more proportional appearance. The accuracy of the pattern, sewing technique, and material selection are crucial elements that influence the quality of the final bustier product. Among the fabric characteristics that significantly affect garment construction, fabric thickness is a key factor. The research aimed to analyze the differences in bustier outcomes made using satin fabrics of different thickness levels—emerald satin (thin), Roberto satin (medium), and bridal satin (thick)—employing the Helen Joseph Armstrong pattern on a mannequin of size M. The methodological approach adopted was experimental, with the independent variable being the thickness of the satin fabric and the dependent variable being the quality of the bustier result. Data were collected through observation sheets evaluated by three expert designers and seventeen trained panelists. The data analysis technique applied involved hypothesis testing using the K-Related test. The findings revealed that the thickness of the satin fabric significantly affects the quality of the bustier. The bustier made from bridal satin achieved the highest average score, namely 84.45% (categorized as very good). Therefore, it can be concluded that the thicker the satin fabric structure, the better the quality of the final bustier result